Oxidation of Proteins in Plants-Mechanisms and Consequences - Sweetlove, L; Moller, I (2009)
The production of reactive oxygen and reactive nitrogen species in plant cells can lead to a variety of modifications of proteins through oxidation of amino acid side groups. The widespread occurrence of such modifications is becoming appreciated as new proteomic approaches allow their systematic identification. Oxidized amino acid residues can be identified directly by mass spectrometry if the modification is stable, but it is more common to covalently tag the oxidized group by reaction with a marker molecule. The marker molecule generally allows visualization through immuno-detection and isolation of modified proteins by affinity purification. Although there are several technical caveats with such approaches, they have been useful in documenting the extent of oxidative modification of proteins and have highlighted a number of proteins where oxidative modification is critical for protein function. A view that such modifications could have signalling ramifications is emerging. However, in many cases there is a lack of information as to the effect of oxidation on protein activity or function. Severe protein oxidation is costly to the cell since oxidatively damaged proteins need to be degraded by specific proteases or damaged cellular components recycled via the autophagy pathway. Avoiding this cost is clearly advantageous, and it has been proposed that proteins may have an over-representation of easily oxidizable amino acids on their surface to act as decoy or sacrificial residues, thus preventing or postponing oxidation of residues more important for the function of the protein. © 2009 Elsevier Ltd. All rights reserved.